Customer fairness perceptions in augmented reality-based online services. (7th December 2021) - Christ-Brendemühl, Sonja; Schaarschmidt, Mario
Abstract : Purpose: An increasing number of retailers is trying to stimulate customers by embedding augmented reality (AR) features such as video try-on into the online shopping experience. As such AR-based online services require customers to actively participate in the service provision, this paper aims at investigating fairness perceptions and customer responses associated with AR-enabled customer participation. Design/methodology/approach: The conceptual framework of this study is based on equity theory. To compare customer responses after an in-store service encounter as opposed to AR-enabled customer participation involving video try-on, this study contains a between-subject online experiment. The effective sample comprises N = 215 participants. Findings: The data analysis demonstrates that AR-enabled customer participation leads to significantly lower levels of distributive, procedural and price fairness as well as lower engagement intentions than in-store service encounters. Simultaneously, participants in the video try-on scenario report higher negative word-of-mouth (WOM) intentions than in the in-store scenario. Research limitations/implications: The extra mile customers go when using AR-based online services is reflected in less favorable fairness evaluations. Practical implications: Service managers should design AR applications in a manner that requires minimum customer participation. Originality/value: This study contributes to service research by linking AR-enabled customer participation to evaluations of distributive, procedural and price fairness and their outcomes. This is vital to fully exploit the potential of AR in services.